Έξυπνες πόλεις και εφαρμογή τους στον Δήμο Λεμεσού - Νικολάου, Νικόλαος (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Smart cities in general are cities which with the use of novel technologies reduce the negative effect they cause on the environment, while at the same time increasing the living standard of their citizens. These smart cities are based on a combination of six characteristics: smart economy, smart mobility, smart environment, smart people, smart living and smart governance. In the context of this study, a literature review takes place with the goal of selecting a set of measures from existing smart cities, which could be applied at the municipality of Limassol. Subsequently, selected measures were analyzed with the objective of showing the improvement they can bring about at the current state of Limassol. The desired improvements revolve around the fields of: energy efficiency, air quality, traffic regulation and green points, where these fields directly or indirectly affect the environment. Afterwards, a questionnaire was created and later filled in by 500 citizens of Limassol, which were selected using the random sampling methodology. The aim of the questionnaire was to extract conclusions regarding the knowledge of the citizens about smart cities, their opinion on which field is the most important and therefore measures should be taken, their opinion on specific measures which they would prefer to be applied and finally their opinion on whether it is feasible to convert Limassol into a smart city. The results of the questionnaire show that the general public has limited knowledge surrounding the concept of smart cities, but this knowledge increases at higher education levels. In addition, the quality of air turned out to be the most important field for measures to be applied. This observation depicts the dissatisfaction of citizens for the bad quality of air in Limassol. Additionally, the same questionnaire was filled in by representatives of three municipalities of Limassol, with the objective of comparing their results to those of the general public. Large deviation in their opinions was observed after comparing their results with the public. Finally, each group, the representatives and the public, blamed the opposing site for not being able to convert Limassol into a smart city.
Keywords: Smart cities; Characteristics of smart cities; Random sampling questionnaire; Έξυπνες πόλεις; Χαρακτηριστικά έξυπνων πόλεων; Ερωτηματολόγιο τυχαίας δειγματοληψίας